2021
DOI: 10.1111/jth.15132
|View full text |Cite
|
Sign up to set email alerts
|

Preventing VTE following total hip and knee arthroplasty: Is prediction the future?

Abstract: Venous thromboembolism (VTE) is a common complication following total hip arthroplasty (THA) and total knee arthroplasty (TKA). Many guidelines advise on the ideal pharmacological thromboprophylaxis strategy; however, despite its use, approximately 1.5% of patients still develop symptomatic VTE. Considering the large number of THAs and TKAs performed worldwide (2.5 million in total), the impact of VTE following these interventions is enormous. This paper discusses a concept how to further lower rates of VTE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…Studies[ 18 – 20 ] have shown that the incidence of DVT in patients treated with THA is 14.13-20.18 %. The results of this study indicate that the incidence of lower limb DVT in patients after THA is 19.78 %, which is lower than the previous report[ 21 , 22 ]. It may be related to the differences in the conditions of included patients, surgical method and perioperative preventive anticoagulation treatment amongst different studies.…”
Section: Discussioncontrasting
confidence: 73%
“…Studies[ 18 – 20 ] have shown that the incidence of DVT in patients treated with THA is 14.13-20.18 %. The results of this study indicate that the incidence of lower limb DVT in patients after THA is 19.78 %, which is lower than the previous report[ 21 , 22 ]. It may be related to the differences in the conditions of included patients, surgical method and perioperative preventive anticoagulation treatment amongst different studies.…”
Section: Discussioncontrasting
confidence: 73%
“…Nearly 2.5 million patients who suffer from joint dysfunction caused by diseases such as hip and knee osteoarthritis undergo arthroplasty surgery each year worldwide ( Nemeth et al, 2021 ). Artificial joint replacement has gained ground as one of the most effective treatments for articular diseases for which conservative approaches fail.…”
Section: Discussionmentioning
confidence: 99%
“…While this score requires external validation, it may be useful in identifying low risk patients who may safely avoid extended prophylaxis. A similar risk assessed approach has been suggested in patients undergoing orthopaedic surgery (35) and has been shown to be successful in cancer patients undergoing chemotherapy (36,37).…”
Section: Discussionmentioning
confidence: 99%